Research on Pressure Control of Hydraulic System for Pump Controlled Anchor Drilling Machine Based on Variable Universe Fuzzy PID Algorithm - Zheng Yan; Guangwei Tang; Youshan Gao (Machines)
To address significant pressure fluctuations in anchor drilling machine systems during the drilling and anchoring support of complex coal roadway surrounding rock, a variable universe fuzzy PID control strategy was proposed to regulate the speed of the servo motor. Additionally, a pump-controlled pressure approach was introduced to further reduce throttling losses and energy consumption. To validate the proposed algorithm, disturbances were simulated by adjusting the opening size of a three-position four-way proportional directional valve. A co-simulation model was first established using AMESIM 2020.1 and SIMULINK R2022a software, followed by experimental verification and comparison with conventional PID control. The experimental results demonstrated that when the system pressure signal was set to a constant value, the proposed algorithm reduced the pressure error by approximately 36.5% compared to PID control. For step pressure inputs, the algorithm decreased the response time and overshoot by 6.8–8.2% and 10.3–16.2%, respectively, under different valve openings. Furthermore, when the system pressure followed various sinusoidal signals, the proposed algorithm exhibited lower pressure error and faster response times than PID control. This study provides theoretical and experimental references for maintaining stable pressure during the operation of anchor drilling machines, offering an efficient and reliable control solution for complex drilling environments.